Design Improvement of Auditorium Seating: A Case Study at Pagoh Education Hub - Hui, Alycia Yap Ching; Mahmood, Salwa; Raja Mamat, Tengku Nur Azila (Human Factors and Ergonomics Society Malaysia (hfem), 2020)
This study is concerned about the auditorium seating design based on the ergonomics concept. Ergonomics is the science of fitting the product to its users or fitting the job to the worker. This study is carried out at Pagoh Education Hub Shared Facility Auditorium. The main objective of this study is to assess the ergonomics posture of users using auditorium’s seating. The poor design of furniture may be possibly cause incorrect posture which will further lead to health problems such as back pain and spinal distortion. The Kinovea software is utilized to measure the posture. Each measurement of different body part posture is assessed by using Rapid Entire Body Assessment (REBA) in order to indicate the risk level of the auditorium’s seating. The REBA score of the existing auditorium’s seating is 7 indicating medium risk which requires further study for improvement. The second objective of this study is to redesign the auditorium’s seating based on the ergonomics concept. The proposed design of auditorium’s seating uses SolidWorks software by referring to the guideline from the Department of Occupational Safety and Health, Ministry of Human Resources Malaysia (DOSH). The desired features such as headrest and armrest are added to the proposed design. The REBA score of the proposed seat design is 3 which indicate significant improvement compared to REBA score of the current design, in terms of ergonomics factors.